PANDANGAN DUNIA IBNU CHAZM Al-ANDALUSY TENTANG KONSEP CINTA (AL-CHUBBUN-NAZHARY) ANALISISSTRUKTURALISME GENETIK TERHADAP TEKS âTHAUQUL-CHAMAÌMAH FIL-ILFAH WAL-ULLAÌFâ - Farhah, Eva; Dardiri, Taufik A; Manshur, Fadlil Munawwar (Universitas Muhammadiyah Surakarta, 2013)
BSTRACT In 404 Hijri / 1014 C, Andalusia of Cordoba su ered chaotic situations not only in politics but also in other segments of life, especially in sex. Free sex ourished and remained arguable. Based on the situation above, Prince Ubaidillah bin Abdurrachman bin al- Mughirah bin Amirul-Muâminin An-Nashir, the grandson of Khalifah An-Nashir, asked Ibnu Chazm Al-Andalusia to write a love story with its complexity in a book. This research elaborates the genetic process of the text âThauqul- ChamaÌmah l-Ilfah wal-UllaÌfâ that is considered a great work by either Arabians or non-Arabians. This work is also considered to be the rst work elaborating love and its complexity as its theme. Furthermore, this research disscusses the view of Ibnu Chazm Al-Andalusy about the concept of love (al-chubbun-nazhary) written in the text. The research adopts genetic structuralism theory with its emphasis on literary text (intrinsic analysis), socio cultural background (historic social reality observation), and the writer. The method is dialectic method, mutual relations between structures of a literary work (the intrinsic features of âThauqul- ChamaÌmah l-Ilfah wal-UllaÌfâ), historic materialism (socio cultural background of Andalusia at the time the work was written), and the writer of âThauqul- ChamaÌmah l-Ilfah wal-UllaÌfâ. Therefore, the âThauqul-ChamaÌmah l-Ilfah wal- UllaÌfâ analysis techniques can be done in three ways: (1) revealing one of the text âThauqul-ChamaÌmah l-Ilfah wal-UllaÌfâ structures by its love concept theme to build up the text and understand the whole structures, (2) revealing socio cultural backgroung of Andalusian people at the time Ibnu Chazm lived and was raised, and (3) revealing the writerâs social groups and their visions by their hipogram and transformation works. This Ibnu Chazmâs vision eventually becomes the embrio of the text âThauqul-ChamaÌmah l-Ilfah wal-UllaÌfâ. The result of the analysis concluded by revealing the issue described in the second and third ways can be used to understand the concept of love in the text âThauqul-ChamaÌmah l-Ilfah wal-UllaÌfâ. Eventually this research reveals that Ibnu Chazmâs direct observation to the people of Andalusia where he lived and was raised initiated the genetic process of the text. He formulated what he gained from his observation to be his vision. This vision became the base of âThauqul-ChamaÌmah Fil-Ilfah wal-UllaÌfâ. The conclusion of the research is that according to Ibnu Chazm, most people relate loves to syahwat, free sex, porns, and things like that. However, hesees talking about love as expressing oneâs tender feeling from the bottom of his heart to nd the truth of love but not to do disgrace and not to do something forbidden by the syariah because love exists in oneâs heart and soul. Meanwhile, Allah SWT holds his heart. Love is about heart and heart belongs to Allah SWT. Therefore, according to Ibnu Chazm, the concept of love must be based on syariah. In another word, the theory of love, the cause of love, expressing love, mantaining love, meeting and âleavingâ the one we love must be based on Al Quran and Hadits. Key Words : Andalusia, Political chaos, Free sex, Genetic structuralism, Dialectic method, Direct observation, Historic reality, Vision, The concept of love based on syariah. Â